Use of a systems engineering framework to assess perceptions and practices about antimicrobial resistance of workers on large dairy farms in Wisconsin - Kates, Ashley E. (medRxiv, 2020)
We studied farmworker practices potentially contributing to transmission of bacteria and antimicrobial resistant genes (ARGs) among animals and farm workers to identify human behavioral interventions to reduce exposure risk. Ten focus groups were conducted on eight farms to explore potentially high-risk practices and farmworker knowledge and experiences with antimicrobial use and resistance using the Systems Engineering in Patient Safety (SEIPS) framework. Farmworkers were asked to describe common tasks and the policies guiding these practices. We found workers demonstrated knowledge of the role of antibiotic stewardship in preventing the spread of ARGs. Knowledge of various forms of personal protective equipment was higher for workers who commonly reported glove-use. Knowledge regarding the importance of reducing ARG transmission varied but was greater than previously reported. Programs to reduce ARG spread on dairy farms should focus on proper hand hygiene and personal protective equipment use but at the level of knowledge, beliefs, and practices.